2003
DOI: 10.1074/jbc.m209824200
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Transport in Norepinephrine Transporters

Abstract: Monoamine transporters, the molecular targets for drugs of abuse and antidepressants, clear norepinephrine, dopamine, or serotonin from the synaptic cleft. Neurotransmitters, amphetamines, and neurotoxins bind before being transported, whereas cocaine and antidepressants bind to block transport. Although binding is crucial to transport, few assays separate binding from transport, nor do they provide adequate temporal or spatial resolution to describe real-time kinetics or localize sites of active uptake. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 54 publications
3
55
0
1
Order By: Relevance
“…9). Because dopamine and other substrates have been shown to bind to the hDAT and related transporters with unchanged affinity even in the absence of Na ϩ (23)(24)(25), this observation strongly supports the idea that the protection of M371C observed only in the presence of Na ϩ is the consequence of a transport-associated conformational change. Data from our previous studies also argue against position 371 being a direct part of the substrate binding crevice.…”
Section: Ent Inhibition Of [supporting
confidence: 72%
See 1 more Smart Citation
“…9). Because dopamine and other substrates have been shown to bind to the hDAT and related transporters with unchanged affinity even in the absence of Na ϩ (23)(24)(25), this observation strongly supports the idea that the protection of M371C observed only in the presence of Na ϩ is the consequence of a transport-associated conformational change. Data from our previous studies also argue against position 371 being a direct part of the substrate binding crevice.…”
Section: Ent Inhibition Of [supporting
confidence: 72%
“…8), we were able to assess whether dopamine protection of this construct was Na ϩ -dependent. Transport is strictly Na ϩ -dependent, but increasing evidence suggests that dopamine and other substrates can bind to hDAT and related transporters with unchanged affinity even in the absence of Na ϩ (23)(24)(25). Accordingly, assessing the Na ϩ dependence of dopamine protection should enable us to distinguish between direct steric protection and a dopamineinduced conformational change that decreases the accessibility of M371C to MTSET.…”
Section: Mtset Inhibits [ 3 H]dopamine Uptake Of M371c and A399c Alsomentioning
confidence: 99%
“…23 Further, the fluorescent analogues of MPP+, ASP+ and APP+, were shown to act as substrates for DAT and other monoamine transporters. [24][25][26]32,33 These observations therefore suggested that a fluorescent analogue of MPP+ might function as an FFN and provided the rationale for the present study.…”
Section: ■ Discussionmentioning
confidence: 62%
“…29 This property was ascribed to light emission quenching via a twisted intramolecular charge transfer (TICT) mechanism, enabled by the perpendicular conformation of the two arene rings. These photophysical properties are shared by the other members of the pyridinium class of dyes, including ASP+, 24 2-(4-dimethylaminostyryl)-N-methylpyridinium (DASPMI), 30 and the FM dyes. 31 Recently, APP+ was also shown to be a substrate for DAT, NET, and SERT, providing a reporter substrate for this important group of plasma membrane transporters and enabling cell-based assays for examining their function and inhibition.…”
mentioning
confidence: 97%
“…1) has been used to stain nerve termini 9 and is a known substrate for the organic cation transporter (OCT). 10 Schwartz et al 11 recently reported that ASP may be used to measure the biophysical properties of monoamine transporters as its accumulation in norepinephrine reuptake transporter (hNET)−expressing cells (measured by fluorescence microscopy) was Na + , Cl − , and temperature dependent. In this article, we describe the use of ASP to develop a microplate-based high-throughput screen for hSERT function, using a microplate fluorimeter.…”
mentioning
confidence: 99%